Increasing rates of quetiapine overdose, misuse, and mortality in Victoria, Australia. (1st June 2018) - Lee, Julia; Pilgrim, Jennifer; Gerostamoulos, Dimitri; Robinson, Jeff; Wong, Anselm
Highlights: Quetiapine-associated poisoning and mortality rates have increased from 2006 to 2016. In 2015, there were nearly 1 million prescriptions for quetiapine dispensed. Increased poisoning rates are strongly correlated with increased prescribing rates. Need to investigate reasons for off-label prescribing by medical practitioners. Abstract: Background: Quetiapine is misused due to its anxiolytic and hedonic effects and has been associated with deliberate self-harm. This study analyzed quetiapine-related calls to the Victorian Poisons Information Centre (VPIC), coronial data from Victorian Institute of Forensic Medicine (VIFM) and prescribed data from the Pharmaceutical Benefits Scheme (PBS) to determine current trends in overdose, misuse and mortality. Methods: This was a retrospective review of multiple databases. Calls to VPIC and coronial data from the VIFM were reviewed from 2006 to 2016. PBS prescription data from 2000 to 2015 was obtained from the Australian Statistics on Medicines website. Results: VPIC data indicated a 6-fold increase in the number of quetiapine-related calls over the 11-year period of which most were overdose-related (77%). Overdose and misuse calls increased by 6-fold and 6.6-fold, respectively. Coronial data also indicated a rise in quetiapine-related harm; a 7.4-fold increase in quetiapine-related deaths was recorded for the same period. Similarly, Australian PBS data showed that quetiapine prescriptions increased 285-fold since 2000. There was a significant positive correlation between the increase in prescribing and overdose (r = 0.75, p < 0.001), and prescribing and mortality (r = 0.82, p < 0.01). Conclusions: This study revealed an increasing trend of misuse, non-fatal and fatal overdoses in Victoria over the last decade. The increasing rates of prescriptions in Australia and thus increased quetiapine availability are likely to have contributed to increased poisoning and mortality. Further research is warranted to explore the reasons behind increased prescribing, including off-label use.